A indexação social na construção discursiva midiática de Jogo de cena - Silva, Marco Donizete Paulino da (2013)
This work is a desk research and was elaborated in order to ascertain to what level is the process of indexing Social within the documentary film, specifically in the discursive construction developed by media around the movie Jogo de cena (Eduardo Coutinho, 2007). It was used the theoretical repertoire pertaining to Information Science to delineate differences between the concepts of indexing and Social Indexing in the field of Social Knowledge Organization and then was observed the direction of the Social Indexing in relation to the field of Documentary filmmaking. His corpus of analysis was based on the movie Jogo de cena, and articles written about the film from its release in 2007, as a method using Content Analysis and Analysis of Moving Images.